Robotic surgery in early and advanced ovarian cancer: Case selection for surgical staging and interval debulking surgery. (January 2023) - Van Trappen, Philippe; de Cuypere, Eveline; Claes, Nele
Abstract: Objective: During the last decade several case series have been published on robotic surgery in early and advanced stage ovarian cancer. Although most studies lack a significant oncological follow-up, more importantly criteria for patient selection for both robotic surgical staging (R-SS) and robotic interval debulking surgery (R-IDS) are not well defined. The objective of this study was to assess the surgical and oncological outcomes, using well-defined selection criteria, between robotic and open surgery in early and advanced stage ovarian cancer. Study design: Single-center retrospective case cohort study including 96 ovarian cancer patients. For early stage ovarian cancer, patients were selected for R-SS after laparoscopic salpingo-oophorectomy of a suspicious adnexal mass. For advanced stage ovarian cancer, only patients receiving neoadjuvant chemotherapy and IDS were included in the study. Exclusion criteria were the presence of residual peritoneal disease after NACT and/or patients requiring additional complex surgical procedures. Results: For early stage ovarian cancer, similar median operative times were seen between R-SS and open surgical staging (O-SS), 132 min and 120 min respectively. Pelvic/para-aortic lymph node yield was similar between R-SS and O-SS, 22/11 nodes and 18/8 nodes respectively. Surgical upstaging occurred in 11.5% in the R-SS group and in 27.6% in the O-SS group. In advanced stage ovarian cancer, the BMI was significantly higher in the R-IDS group compared to the O-IDS group (27.8 vs 23.5; p =.006). The median follow was 52 months in the R-IDS group and 31 months in the O-IDS group. Recurrent disease occurred in 42.9% of the R-IDS group and in 45% of the O-IDS group. The length of hospitalization was significantly longer in the O-SS and O-IDS group (p <.00001). Conclusion: Patients with clinically early stage ovarian cancer, confirmed after laparoscopic removal of a suspicious adnexal mass, are candidates for R-SS whilst maintaining similar surgical and oncological outcome measures as O-SS. In advanced ovarian cancer, suitable candidates for R-IDS are those who receive NACT with good response and no residual peritoneal disease, especially in patients with a high BMI, but large prospective randomized trials with well-defined criteria are needed.